The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.aop.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

RG flows of Quantum Einstein Gravity in the linear-geometric approximation

Abstract: a b s t r a c tWe construct a novel Wetterich-type functional renormalization group equation for gravity which encodes the gravitational degrees of freedom in terms of gauge-invariant fluctuation fields. Applying a linear-geometric approximation the structure of the new flow equation is considerably simpler than the standard Quantum Einstein Gravity construction since only transverse-traceless and trace part of the metric fluctuations propagate in loops. The geometric flow reproduces the phase-diagram of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
88
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 143 publications
(304 reference statements)
13
88
1
Order By: Relevance
“…So when we go through the usual procedure and define the associated EAA, the derivation of ∂ k Γ k ≥ 0 in the main part of this paper applies to it, provided the above exact compensation of the ghost and V µ contributions persists in presence of an IR cutoff. While this is not the case for a generic cutoff, it has been shown [92] that if the cutoff operators R k of the ghost and metric fluctuations, respectively, are appropriately related, which always can be achieved, the compensation does indeed persist. For further details the reader is referred to [92].…”
Section: Jhep03(2015)065mentioning
confidence: 98%
See 1 more Smart Citation
“…So when we go through the usual procedure and define the associated EAA, the derivation of ∂ k Γ k ≥ 0 in the main part of this paper applies to it, provided the above exact compensation of the ghost and V µ contributions persists in presence of an IR cutoff. While this is not the case for a generic cutoff, it has been shown [92] that if the cutoff operators R k of the ghost and metric fluctuations, respectively, are appropriately related, which always can be achieved, the compensation does indeed persist. For further details the reader is referred to [92].…”
Section: Jhep03(2015)065mentioning
confidence: 98%
“…While this is not the case for a generic cutoff, it has been shown [92] that if the cutoff operators R k of the ghost and metric fluctuations, respectively, are appropriately related, which always can be achieved, the compensation does indeed persist. For further details the reader is referred to [92]. Thus we have shown that (at the very least) when the ghosts are the only Grassmannodd fields it is in principle always possible to set up the gauge fixing and ghost sector of the EAA and its FRGE in such a way that ∂ k Γ k ≥ 0 holds true pointwise.…”
Section: Jhep03(2015)065mentioning
confidence: 98%
“…Finally, the total Wilsonian effective action can be written 17) and C k (p) is an ultraviolet cutoff profile for this effective action and effective partition function, which regularises at scale k. C k (p) has to satisfy the same conditions asC Λ (p) above (with the replacement Λ → k of course). Since the functional integral with this action S tot,k is therefore already completely regularised in the ultraviolet, there is no need for any dependence on the overall UV cutoff Λ.…”
Section: Jhep11(2015)094mentioning
confidence: 99%
“…[2], there is a wealth of literature investigating asymptotic safety in this way. For reviews and introductions see [10][11][12][13][14], and for recent advances see for example [15][16][17][18][19][20][21][22][23][24]. In the vast majority of this work the RG flow equation takes the generic form [3]:…”
Section: Introductionmentioning
confidence: 99%
“…However this is also an area where there is little guidance from current experimental observation or other techniques, and therefore one must place particular reliance on a rigorous understanding of the mathematical structure that the exact RG exposes, in so far as this is possible. This is especially so with recent work on "functional truncations" [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%